Host-Range Restrictions of Murine Leukemia Viruses in Mouse Embryo Cell Cultures - Hartley, Janet W. (1970)
Murine leukemia virus strains fall into three categories with respect to their ability to propagate in cells of National Institutes of Health (NIH) Swiss and BALB/c mouse embryos. Cultures of NIH cells are 100- to 1,000-fold more sensitive to “N-tropic” strains than BALB/c cell cultures, but are 30- to 100-fold less sensitive to “B-tropic” strains. Some virus strains (dually tropic or “NB-tropic”) propagate equally well in both cells. M-MSV pseudotypes show the host-range characteristics of the virus supplying the envelope, both in vitro and in vivo. The host-range characteristics appear to be genetically determined and could not be explained by host-induced modification or virus mixtures. There was no correlation between host range and Gross-AKR or FMR serotype.